A Proactive Approach is Needed to Address the Impact of Emotional Labour in Public Libraries - Julia Hayes (Evidence Based Library and Information Practice, 2026)
A Review of: Rodger, J., & Erickson, N. (2025). Leadership perspectives on emotional labour in large urban public libraries. Canadian Journal of Information and Library Science, 48(2), 108–120. https://doi.org/10.5206/cjils-rcsib.v48i2.22897 Objective – To explore middle managers’ knowledge about emotional labour and how their knowledge impacts the way they support their staff in the workplace. Design – Semi-structured interviews. Setting – Three large, urban public library systems in Canada. Subjects – 27 middle managers. Methods – The researchers conducted interviews online via videoconferencing software. Interviews were recorded, transcribed, and analyzed qualitatively using thematic analysis. Main Results – The participants of the study articulated varied understandings of emotional labour and how it related to their role as leaders in the workplace. Many participants were aligned in identifying the undervalued and often unspoken nature of emotional labour, while also recognizing it as central to their role as middle managers. Equipped with styles of leadership that centred communication, collaboration, support, and employee autonomy, participants employed a variety of techniques, including check-ins, boundary setting, and emotional validation to support their staff’s emotional well-being; however, many noted that inconsistent support from senior leadership prevented them from addressing systemic problems that were at the root of their staff’s concerns. Participants also cited a lack of formal structures of support for middle managers while negotiating the competing expectations of staff, upper management, and patrons as contributing to increased emotional strain. Feelings of alignment with the organizational goals of their library and support from upper management varied among participants and impacted how well participants felt they were able to manage their staff’s and their own experiences of emotional labour. Conclusion – The study revealed a need for libraries to be proactive in how they address the impacts of emotional labour experienced by leaders and staff. Recommendations for this proactive approach include increased support for middle managers, recognition of the collective responsibility of addressing emotional labour, embedded training programs, and the prioritization of authentic leadership and emotional intelligence.